Efektivitas Media Digital Storytelling Berbasis Tradisi Lisan NTB terhadap Fluency dan Confidence Speaking Siswa - Muliadi, Mul (Primary Journal of Multidisciplinary Research, 2025)
This study aims to examine the effectiveness of digital storytelling media based on the oral traditions of West Nusa Tenggara (NTB) in improving students’ speaking fluency and confidence in English learning. The research is grounded in the need for instructional models that not only enhance speaking skills but also integrate culturally relevant content to create more meaningful learning experiences. A quasi-experimental design with a pretest–posttest control group was employed. The sample consisted of two classes of junior high school students selected through cluster random sampling. The experimental group was taught using digital storytelling media developed from NTB folktales (such as Legenda Putri Mandalika and Gumi Paer Lombok), while the control group received conventional instruction without digital elements or local cultural content. Data were collected using a speaking fluency rubric (covering fluency, pauses, accuracy, and speech rate) and a Likert-scale questionnaire assessing speaking confidence. Data analysis employed paired sample t-tests and independent sample t-tests. The results indicate a significant difference in students’ speaking fluency and confidence between the experimental and control groups (p < 0.05). The implementation of NTB-based digital storytelling was found to provide a more engaging learning experience, increase student participation, and strengthen cultural identity within English language learning. In conclusion, digital storytelling media based on NTB oral traditions is effective in enhancing students’ speaking fluency and confidence, making it a recommended innovative and contextually relevant learning medium for Indonesian schools